1997
DOI: 10.1016/s0885-3924(97)00020-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma morphine and glucuronide (M3G and M6G) concentrations in hospice inpatients

Abstract: Plasma morphine, morphine-3-glucuronide (M3G), and morphine-6-glucuronide (M6G) concentrations were quantified by high performance liquid chromatography (HPLC) in 36 hospice inpatients receiving morphine orally or subcutaneously. The data were analyzed in relation to dose, serum creatinine, serum gamma glutamyl transferase, and presence or absence of opioid-induced adverse effects. There were significant associations (P < 0.05) between plasma morphine, M3G (subcutaneous route only), and M6G concentrations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 41 publications
2
56
1
2
Order By: Relevance
“…A study of cancer patients found no correlation between cognitive impairment and the morphine-6-glucuronide-to-morphine ratio [101]. In a small case series of hospice patients with morphine-related side effects, including cognitive impairment and nausea, morphine metabolite levels were elevated compared with controls, but it was not possible to establish the relative contribution of renal impairment and elevated metabolite levels to these side effects [4]. Although the plasma concentration of opioid metabolites has not been studied in relation to dehydration or volume deficit states, it is logical to assume that opioid metabolite levels would be elevated in these states, owing to their increased concentration in a reduced intravascular volume, and possibly also because of their reduced renal excretion.…”
Section: Fluid Deficit State: Pathophysiology and Pathogenesismentioning
confidence: 95%
“…A study of cancer patients found no correlation between cognitive impairment and the morphine-6-glucuronide-to-morphine ratio [101]. In a small case series of hospice patients with morphine-related side effects, including cognitive impairment and nausea, morphine metabolite levels were elevated compared with controls, but it was not possible to establish the relative contribution of renal impairment and elevated metabolite levels to these side effects [4]. Although the plasma concentration of opioid metabolites has not been studied in relation to dehydration or volume deficit states, it is logical to assume that opioid metabolite levels would be elevated in these states, owing to their increased concentration in a reduced intravascular volume, and possibly also because of their reduced renal excretion.…”
Section: Fluid Deficit State: Pathophysiology and Pathogenesismentioning
confidence: 95%
“…These studies have consistently demonstrated elevated metabolite levels 88,89,92,[101][102][103][104][105][106] when measured in renal impairment. They also have suggested a frequent association between renal impairment and opioid toxicity.…”
Section: Pathophysiology Of Opioid-associated Cognitive Dysfunctionmentioning
confidence: 91%
“…We speculate that the lack of a clear, linear inversely proportionate relationship between amount of opioid administered and need for additional analgesia when asked reflects the tremendous amount of interpatient variability in opioid requirement. 16,28,29 This is presumably driven, at least in part, by substantial differences in the "objective" magnitude of the painful stimulus; its subjective perception; and the poorly understood Values are n (%) unless otherwise noted. NRS = numeric rating scale.…”
Section: 21-24mentioning
confidence: 99%